Influence of resin system on the energy absorption capability and morphological properties of plain woven kenaf composites - Salman, Suhad D.; Leman, Zulkiflle; Hameed Sultan, Mohamed Thariq; Ishak, Mohamad Ridzwan; Cardona, Francisco (IOP Publishing, 2015)
Due to both environmental and technical advantages, natural fibers are being used as reinforcement of polymeric composite in many industries. The flexibility of the most natural fibers is one of the important technical characteristic which allows them to resist impact forces. An investigation was carried out to compare the energy absorption capability of kenaf/PVB film and kenaf/epoxy composites. The hot and cold press techniques were used to fabricate the specimens with 35% kenaf fibre weight fraction. The charpy impact test was performed on forty notched specimens using a pendulum impact tester with different hammer energy. The results showed that the kenaf/PVB film composite has the highest energy absorption, strength and toughness compared with the epoxy composite. At high energy levels, the impact strength and toughness of the kenaf/PVB film was six times of kenaf/epoxy composite. In addition, the scanning electron microscopy was assessed to demonstrate the different failure in fracture surfaces. It was found that the kenaf/PVB film composite failed by fibre fracture while kenaf/epoxy composite failed by a combination of fibre pull-out and fibre fracture as well as crack propagations through the matrix.